BENTUK ANIMASI 3 DIMENSI DALAM MENDUKUNG PEMROSESAN INFORMASI - Deni Darmawan (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2012)
This study is a breakthrough in supporting students’ sd, SMP, AND high school in the SouthGarut in performing information processing of learning both for the exact and social. The study tries toanswer the question of how large the focus of information-processing speed of the student learningbased on element formation 3dimensi animation on the exact and social subjects (IPS). The study wasconducted on students at elementary, junior high, and high school. The study was conducted by usingthe method of research and development carried out experiments in which this research is consideringthe second year in which the CAI instructional model and formation animation 3dimensi been designedbefore. The study was conducted at the elementary school level, junior high, and high school located inthe southern Garut, with through stratified random sampling. The results showed that the speed ofinformation processing of learning both exact and social groups (IPS) conducted junior high schoolstudents were more superior than the elementary or high school students, through Computer AssistedInstruction teaching model loaded with animation 3dimensi formation.